2020
DOI: 10.1016/j.midw.2020.102840
|View full text |Cite
|
Sign up to set email alerts
|

Swedish midwives’ experiences and views of amniotomy: An interview study

Abstract: Objective To explore midwives’ experiences and views of amniotomy. Design A qualitative inductive design was used. Data were collected using interviews and analysed with content analysis carried out with NVivo 12. Setting and participants Sixteen midwives working at delivery wards at three hospitals in the south of Sweden. Findings Three categories emerged: “Promote, protect and support the physiological process of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 24 publications
(37 reference statements)
0
17
0
Order By: Relevance
“…Further, mechanical methods are recommended, rather than medical, for the induction of labor in women with a previous cesarean section, 27,28 and therefore possibly "riskier" amniotomies are performed in this group. 9 Induction of labor was also a risk factor for UCP in both labors with an amniotomy and those with SROM. Boyle & Katz 29 reported the same in a study including data from 1995 to 2001, as so did Kahana et al 2 with data from 1988 to 1999.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Further, mechanical methods are recommended, rather than medical, for the induction of labor in women with a previous cesarean section, 27,28 and therefore possibly "riskier" amniotomies are performed in this group. 9 Induction of labor was also a risk factor for UCP in both labors with an amniotomy and those with SROM. Boyle & Katz 29 reported the same in a study including data from 1995 to 2001, as so did Kahana et al 2 with data from 1988 to 1999.…”
Section: Discussionmentioning
confidence: 97%
“…As polyhydramnios is an indication for induction of labor, it is likely that this group undergoes amniotomy more often than parturients without polyhydramnios. Previous studies have suggested performing a “controlled amniotomy” in cases of an unengaged presenting part, as is often the case in the presence of polyhydramnios, by “needling” the amniotic bag, for a slower release of the fluid, and to give mild fundal pressure to assist the presenting part down into the pelvis 6,9 . This is likely used clinically; however, to the best of our knowledge, there are no studies evaluating the benefits and safety of this method.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study, midwives working at an University hospital experienced that amniotomy was performed due to a constant high work load, therefore we used stratification in order to investigate this issue [ 28 ]. Our results in the present study show variations in the prevalence of amniotomy between Swedish hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…A first step in addressing an inappropriate use of labor interventions is to explore regional variations in the prevalence within the country [ 8 ]. It is of importance to acknowledge that amniotomy is performed for several reasons, occasionally laboring women even request it, as described in our previous study [ 28 ]. This fact may contribute to differences in the prevalence between hospitals.…”
Section: Discussionmentioning
confidence: 99%